2010
DOI: 10.1159/000297734
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychobiological Aspects, Comorbidity Patterns and Dimensional Models in Borderline Personality Disorder

Abstract: Borderline personality disorder (BPD) is a comorbid and disabling condition with high prevalence in psychiatric settings. The pathogenesis of BPD involves complex interactions among genetic, neurobiological and environmental factors, resulting in multiple core symptom domains such as emotional dysregulation, impulse dyscontrol, aggression, cognitive dysfunctions and dissociative states. Neurobiological studies show that symptoms and behaviors of BPD are partly associated with alterations in glutamatergic, dopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 209 publications
4
34
0
Order By: Relevance
“…The putamen and the basal ganglia are involved not only in planning and execution of movement, but also in higher cognitive functions, such as attention and decision-making, 61 which at least in some studies have been reported to be impaired in patients with BPD. 62 We also found reduced grey matter in the cerebellar vermis. Recent findings suggest a major involvement of cerebellar structures in emotional behaviour, 63 which is mediated by reciprocal connections to structures of the limbic system.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The putamen and the basal ganglia are involved not only in planning and execution of movement, but also in higher cognitive functions, such as attention and decision-making, 61 which at least in some studies have been reported to be impaired in patients with BPD. 62 We also found reduced grey matter in the cerebellar vermis. Recent findings suggest a major involvement of cerebellar structures in emotional behaviour, 63 which is mediated by reciprocal connections to structures of the limbic system.…”
Section: Discussionsupporting
confidence: 54%
“…Changes in grey matter volume in the parietal lobe could explain attentional capacity deficits described in patients with BPD. 62 The Heschl gyrus is located in the primary auditory cortex and is involved in the processing of auditory information. 71 Studies addressing the involvement of the auditory system in patients with BPD have been scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Much research has focused on structural and functional abnormalities in brain areas related to emotion and impulsivity, and these areas may also serve as endophenotypes for BPD, although they are not always presented as such. Lis et al [47], Goodman et al [48•], and Dell'Osso et al [49] reviewed neuroimaging and neurobiological studies of BPD and found evidence for both structural and functional abnormalities in the brain areas of individuals with BPD, including the hippocampus, amygdala, anterior cingulate cortex, prefrontal cortex, and orbitofrontal cortex. These endophenotypes may influence the traits that underlie BPD symptoms (eg, emotion dysregulation, poor cognitive control), and for this reason, insight into these factors promises to add to the development of a more comprehensive (dimensional) classification of BPD.…”
Section: Endophenotypesmentioning
confidence: 99%
“…While emotional dysregulation is a core feature of BPD itself, it may also be an important candidate to explain high rates of comorbidity between BPD and other mental disorders (e.g. substance use disorders and affective disorders) (Dell'Osso et al, 2010).…”
Section: Introductionmentioning
confidence: 99%